X-RAY AND ULTRASONOGRAPHICAL CRITERIA OF PREDICTION OF UNFAVOURABLE COURSE OF THE SYNOVITUS OF THE HIP JOINT IN CHILDREN DURING THE INITIAL EXAMINATION - Сергей Иванович Головкин; Владимир Александрович Уткин; Евгений Михайлович Кравец; Никита Андреевич Шабалдин (The Publishing House Medicine and Enlightenment, 2016)
Parameters of Xray and Sonographical examination of 56 children with transitory synovitus of the hip joint have been analyzed. Separately estimated observation in 3 age groups: 2-4 years, 5-7 years and over 7 years. In accordance with the x-ray we have calculated epiphyseal Index (EI) and epiphyseal coefficient. Proposed epiphyseal asymmetry index (EA). In accordance with the ultrasonic examination data, we have defined 3 stages of joint disease. The first stage is characterized with minimal changes in the affected joint, the second stage showed synovitus of joint, the third - with signs of morphological destruction. In case of visible reduction of height of femoral head epiphysis we recommend calculating EI and evaluate EA.